Indicadores de irrigação e para autogestão do Distrito de Irrigação do Projeto Tabuleiros de Russas, CE - Pontes, Antonio Erildo Lemos (2024)
The study was conducted at Tabuleiros de Russas Irrigation Project, managed by Tabuleiros de Russas Irrigation District (Distar). The main goal was to assess irrigation performance at the plot level and the district's self-management capability. Specific objectives included analyzing Relative Irrigation Supply (FRI), evaluating primary irrigation systems in use, and assessing Irrigation District performance indicators from a self-management perspective. These evaluations are essential due to various changes in Brazil's irrigation sector and significant public investments in irrigation projects. Water management at the plot level was analyzed using the Relative Irrigation Supply (FRI) indicator. Irrigation systems were assessed using Christiansen Uniformity Coefficient (CUC), Distribution Uniformity Coefficient (CUD), and Statistical Uniformity Coefficient (CUE). To evaluate the self-management capacity of Irrigation District, several performance indicators were analyzed: Self-sustainability, Cost per Hectare in Production, Percentage of Production needed for Operation and Maintenance (O&M), Revenue Generation per Hectare (IGRH), Water Productivity (PAir), Land Utilization Coefficient (CUT), and Water Fee Default Rate (K2). Results led to the following conclusions: Relative Irrigation Supply values, especially in small producers' plots, indicate empirical irrigation practices with a tendency to overwater. This highlights the need for training and raising awareness among farmers about rational water use. Water distribution uniformity in about 60% of evaluated irrigation systems ranged from reasonable to poor, indicating underperformance and a need for awareness regarding efficient irrigation in the production system. The water crisis from 2012 to 2017 that caused a 66.2% reduction in irrigated area highlighted the lack of water reliability to support expansion of cultivated areas in Tabuleiros de Russas Irrigation Project. This situation significantly increased challenges in achieving financial self-management for the Irrigation District.